Impact of crystalline type on starch-polyphenol complexation under sequential gelatinization and ultrasonication - Sandra Kusumawardani; Naphatrapi Luangsakul (Ultrasonics Sonochemistry, 2026)
Inhibiting starch digestion is an effective approach to regulate postprandial blood glucose levels, and ultrasound assisted modification has emerged as a promising non-thermal strategy to tailor starch structure and functionality. In this study, sequential treatment of gelatinization and ultrasonication at varying amplitudes were employed to assess the impact of the interaction between different types of starch crystallinity (A, B, and C type) with red rice bran polyphenols. The results demonstrated moderate amplitude at 60% provided optimal ultrasound condition, significantly enhancing polyphenol binding and promoting molecular rearrangement across all starch types. B type starch exhibited the highest polyphenol binding capacity. In contrast, A and C type starches showed more pronounced increases in crystalline order and thermal stability, indicating stronger molecular reorganization under ultrasound stress. X-ray diffraction revealed no new peaks among all starch types, indicating that complexation occurred via non V-type interactions. Amplitude of ultrasound at 60% effectively reduced rapidly digestible starch while increasing slowly digestible and resistant starch fractions, resulting in a lower estimated glycemic index within the medium range (65-68). These findings elucidate the role of ultrasonic cavitation in modulating starch-polyphenol interactions and demonstrate how starch crystalline structure governs complexation behavior and digestion resistance. Overall, the present study contributes a promising strategy for the development of functional food ingredients, particularly for slowing down the digestibility.
Keywords: Food composition and properties; Microencapsulation and Drying Processes; Proteins in Food Systems